(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
A review of Laura A. Dickinson, Outsourcing War and Peace: Preserving Public Values in a World of Privatized Foreign Affairs. (New Haven and London: Yale University Press, 2011).